Cultural education of adults in theory and research in Poland after '89 - selected aspects - Sylwia Słowińska (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2017)
The article is a review and its goal is to present the most typical views on the cultural education of adults developed by the Polish researchers since 1989 as well as to outline its empirical picture. In the first part of the article the author describes ways of understanding cultural education within the framework of Polish classical (traditional) and non-traditional concept of cultural education. Then it is shown that with the spreadof the broad way of understanding education as a lifelong process, adults appeared in the concepts of cultural education as its participants and addressees. However, none of the Polish concepts is focused on the adults only. In the second part of the article there are presented the characteristics and trends of cultural education of adults in Poland, reconstructed on the basis of studies conducted in recent years. In conclusion, the author emphasizes the need to develop research in this area, which after 1989 in Poland, was outside the mainstream of interest of researchers on adult education and requires in-depth test to identify and understand transformation taking place within it